Physical Properties of Chilli Sauce as Affected by Different Concentration of Water Yam’s Starch - Ulyarti; Nazarudin; Astrini; ali, lisani (Department of Technology of Agricultural product (THP) Jambi University, 2019)
Abstract—The aim of this research was to determine the effect of purple water yam’s starch concentration on the physical properties of chili sauce. This study used a completely randomized design consisted of 5 levels concentration of purple water yam’s starch (0, 1, 2, 3 and 4%) and four replications. ANOVA showed that the concentration of purple water yam’s starch significantly affected the sauce viscosity and syneresis but did not affect the aroma and color of the sauce. Among the levels of starch concentration used as treatment, the concentration of 2% purple water yam’s starch produced chilli sauce with the best physical properties with viscosity of 48.75 Poise and syneresis 2.14%. Keywords— purple water yam; starch; chilli sauce; physical properties